Antimicrobial Bioactivity and GC-MS Analysis of Different Extracts of Corchorus olitorius L Leaves - Nakaziba, Rebecca; Amanya, Sharon B.; Sesaazi, Crispin D.; Byarugaba, Frederick; Ogwal-Okeng, Jasper; Alele, Paul E. (The Scientific World Journal, 2022)
Background and Aim. Plants have been used for the treatment of infectious diseases among various communities worldwide with undeniable success. Corchorus olitorius L is used to treat various ailments including infections. However, there are limited data regarding its antimicrobial spectrum in Uganda. In the bid to bridge this gap, we investigated the antimicrobial bioactivity of Corchorus olitorius L against Candida albicans, Staphylococcus aureus, Streptococcus pneumoniae, Escherichia coli, and Mycobacteria tuberculosis. Methods. Corchorus olitorius L leaves were harvested, air-dried, and serially extracted using diethyl ether, methanol, and distilled water (aqueous). e crude extracts and their components separated by TLC were assayed for bioactivity against the organisms mentioned above using the agar well di usion technique. Chloramphenicol was used as a positive control. Observation of a zone of inhibition indicated bioactivity. Finally, the components that displayed bioactivity were subjected to GCMS analysis to establish their chemical composition using the MS library database. Results. Crude extracts of Corchorus olitorius L leaves and their TLC-separated components demonstrated bioactivity against Staphylococcus aureus (14 mm), Streptococcus pneumoniae (16 mm), and Escherichia coli (11 mm) but neither against Candida albicans nor Mycobacteria tuberculosis. However, the overall zones of inhibition were smaller compared to the positive control ( 18 mm). GC-MS analysis of the active components revealed the presence of methyl esters. Conclusion. Corchorus olitorius L is bioactive against both Gram-negative and Grampositive bacteria but neither against fungi nor mycobacteria. e bioactivity is attributable to the presence of methyl esters. Since methyl esters already have proven bioactivity in some studies, they could be further studied and optimized for possible pharmaceutical use. Further, to provide a more comprehensive antimicrobial spectrum of Corchorus olitorius L in Uganda, puri ed active components could be investigated using a wider range of organisms.
Keywords: Antimicrobial Bioactivity; Corchorus olitorius